The Role of Creative Arts Therapy in Supporting the Mental Health of Veterans Returning to School - Kuang, Xinyue (Frontiers in Humanities and Social Sciences, 2024)
As an increasing number of veterans opt to resume their studies, the psychological and social obstacles they encounter in adjusting to campus life and the social milieu are becoming more pronounced. The objective of this study is to examine the impact of integrated music and painting therapy on the psychological well-being and social adaptation of military personnel who have resumed their studies. The study subjects were eight re-enrolled military personnel enrolled in Jiangxi Software Vocational and Technical University. The impact of a two-hour art-integrated therapy intervention on the subjects' mental health was assessed through the measurement of changes in depression, anxiety, and stress levels. The findings revealed a notable decline in the participants' mental health indicators following the art therapy intervention, suggesting that art therapy is an effective approach for addressing the psychological challenges faced by re-enrolled military personnel. Moreover, art therapy enhanced their social skills and self-identity, thereby facilitating their adaptation to campus life. In light of these findings, it is recommended that integrated music and painting therapy be promoted in higher education institutions and veterans' service centers to facilitate the comprehensive psychological and social rehabilitation of a greater number of veterans.